Multiple Osmotic Stress Responses in Acidihalobacter prosperus Result in Tolerance to Chloride Ions - Dopson, Mark; Holmes, David S.; Lazcano, Marcelo; McCredden, Timothy J.; Bryan, Christopher G.; Mulroney, Kieran T.; Steuart, Robert; Jackaman, Connie; Watkin, Elizabeth L. J. (Frontiers in Microbiology, 2017)
Extremely acidophilic microorganisms (pH optima for growth of ≤3) are utilized for the extraction of metals from sulfide minerals in the industrial biotechnology of ‘biomining’. A long term goal for biomining has been development of microbial consortia able to withstand increased chloride concentrations for use in regions where freshwater is scarce. However, when challenged by elevated salt, acidophiles experience both osmotic stress and an acidification of the cytoplasm due to a collapse of the inside positive membrane potential, leading to an influx of protons. In this study, we tested the ability of the halotolerant acidophile Acidihalobacter prosperus to grow and catalyze sulfide mineral dissolution in elevated concentrations of salt and identified chloride tolerance mechanisms in Ac. prosperus as well as the chloride susceptible species, Acidithiobacillus ferrooxidans. Ac. prosperus had optimum iron oxidation at 20 g L-1 NaCl while At. ferrooxidans iron oxidation was inhibited in the presence of 6 g L-1 NaCl. The tolerance to chloride in Ac. prosperus was consistent with electron microscopy, determination of cell viability, and bioleaching capability. The Ac. prosperus proteomic response to elevated chloride concentrations included the production of osmotic stress regulators that potentially induced production of the compatible solute, ectoine uptake protein and increased iron oxidation resulting in heightened electron flow to drive proton export by the F0F1 ATPase. In contrast, At. ferrooxidans responded to low levels of Cl- with a generalized stress response, decreased iron oxidation, and an increase in central carbon metabolism. One potential adaptation to high chloride in the Ac. prosperus Rus protein involved in ferrous iron oxidation was an increase in the negativity of the surface potential of Rus Form I (and Form II) that could help explain how it can be active under elevated chloride concentrations. These data have been used to create a model of chloride tolerance in the salt tolerant and susceptible species Ac. prosperus and At. ferrooxidans, respectively.